RETRACTED: Boundary value problems of degenerate integro-differential equations on the boundary of the region with application in filtration - Abdurazakov Abdujabbor; Fozilov Anvarjon; Makhmudova Nasiba; Mirzamakhmudova Nilufar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001